Anti-flatulence treatment and status epilepticus: a case of camphor intoxication. Issue 12 (20th November 2007) - Guilbert, J; Flamant, C; Hallalel, F; Doummar, D; Frata, A; Renolleau, S
Abstract : We describe a case of a young child who lived in Hong Kong who presented with a severe epilepticus status after a return flight to Paris. Routine laboratory tests failed to establish a cause. Upon further questioning, the parents reported that the nanny had given an abdominal massage to the child with an unlabelled solution reported to have anti-flatulence effects. Toxicological analysis of this solution revealed the presence of camphor. Although the highly toxic effects of camphor have long been established, the present case illustrates that camphor continues to be a source of paediatric exposure. This case highlights the importance of systematic questioning and recalls the extreme danger associated with camphor even when administered transcutaneously.